4 - The Academy and its Disengagement from Popular Struggles in Kenya - Godwin R. Murunga, (Journal of Higher Education in Africa, 2010)
This is a study of the academy and its disengagement from popular struggles in Kenya. Focusing attention on the role of faculty unions and student associations, the study identifies and describes the trajectory of engagement and concludes that the current conjuncture tends more towards disengagement from popular struggles by unions and associations, many of which are consumed by daily struggles for staff and student welfare and nothing else. Thus the pattern has moved from active participation in popular struggles against authoritarian one-party rule to the current phase in which the terrain of higher education is at a crossroads. Academics and students remain disengaged from everyday political struggles in society and the possibilities of a re-composition of the student movement and faculty union are many. The study explains why the potential for greater involvement of universities as change agents in the diverse struggles for social justice remain under-utilised.